Tertúlia literária dialógica : a aprendizagem dialógica no testemunho docente - Sanches, Camila Angelica Silvestrini [UNIFESP] (2016)
The dialogical learning, conceptual basis of the dialogic communicative acts in the process of interactive text interpretation is the central reference to this piece of work. The concept of dialogic learning, set first for Flecha (1997), has references for Paulo Freire's dialogicity as well as the theory of communicative action by Jürgen Habermas. Nowadays, this concept is also a reference to the proposal of the learning communities (CL). The CL s form a new concept of school, open to the participation of the other members of the community in which the Dialogic Literary tertulias take place. The problematic which moves this present study spins around the question: Is the dialogic literary tertulia (dlt) contributing to the development of a more dialogical relation inside the school and also to the teaching/learning process? It's important to make it clear here that the interest in the issue mentioned before, raised from my experience as a teacher in elementary and high schools together with the perseption that the learning process lack of dialogue, and when i say dialogue I mean it as an egalitarian dialogue. It`s random when we think of an education system which values all the people involved, but has implications for the education process firmed in principles for the emancipation of the individuals. The present study discussing carry dialogues and analyse, together with a teacher of a State School of Sao Paulo, about the possible changes which took place inside the school, especially those concerning the relationship between teacher and student and the teaching /learning process after the use of dialogical practices in Dialogical Literary tertulias carried out inside the school, analyse the excluding and the transformation dimensions in the dialogue with the teacher, identifying the barriers to the dialogicity between teacher and student, analyse in Paulo Freire`s main writings the concept of dialogicity, reflecting upon the main contributions in the teaching/learning process, aiming at an education of better quality, in Freirean sense, verify and identify in the teachers talking the seven principles of the Dialogical Learning. As a proposal to the methodological path we adopted the testimonial collection, using a guide of a semi-structured 21-questions. After transcribing the data, the organization and the analyse was performed with the help of the teacher who was interviewed. This research has as a justification in the importance of the reflection and analyse of the education reality of a Brazilian state school in which the Dialogical Literary tertulia takes place, in view of the relevance of the pedagogical proposal in the Dialogical Learning.